2021
DOI: 10.1108/ijchm-01-2021-0102
|View full text |Cite
|
Sign up to set email alerts
|

A wearable technology solution and research agenda for housekeeper safety and health

Abstract: Purpose Adopting an interdisciplinary perspective, the purpose of this paper was to posit an industry-wide technological intervention for hotel housekeeper safety and health through the advancement of wearable technology. Design/methodology/approach Using the task-technology fit (TTF) model and examples of successful safety and health applications of wearable technologies in the health-care and construction management industries, interventions and future research directions are presented to address workplace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 101 publications
0
16
0
Order By: Relevance
“…Heating, ventilation, and air conditioning (HVAC) systems are defined as systems that consist of a collection of control loops that work together to perform the tasks required to maintain the required environmental conditions as precisely as possible, help approximate temperature and humidity, and improve indoor air quality in the building (Buhalis & Moldavska 2021). Many types of smart services technologies are used in hotels such as: wearable technology is a technology that allows the user to link it to a cell phone or computer using android devices, which allows them to click on the notification on the watch by issuing smartwatches to its employees, combined with task management software to help speed service by responding to its messages and improving communication with the guest and its efficiency (Abdelmoaty & Soliman, 2020;Mejia et al, 2021). Guests sleep, so a watch or bracelet with vibration (used in Western hotels) can wake them up; additionally, the wristband can pass hotel room keys (Stankov et al, 2019).…”
Section: In-room Control Systemsmentioning
confidence: 99%
“…Heating, ventilation, and air conditioning (HVAC) systems are defined as systems that consist of a collection of control loops that work together to perform the tasks required to maintain the required environmental conditions as precisely as possible, help approximate temperature and humidity, and improve indoor air quality in the building (Buhalis & Moldavska 2021). Many types of smart services technologies are used in hotels such as: wearable technology is a technology that allows the user to link it to a cell phone or computer using android devices, which allows them to click on the notification on the watch by issuing smartwatches to its employees, combined with task management software to help speed service by responding to its messages and improving communication with the guest and its efficiency (Abdelmoaty & Soliman, 2020;Mejia et al, 2021). Guests sleep, so a watch or bracelet with vibration (used in Western hotels) can wake them up; additionally, the wristband can pass hotel room keys (Stankov et al, 2019).…”
Section: In-room Control Systemsmentioning
confidence: 99%
“…IoT, robots and artificial intelligence could enhance visitors' experiences and the quality of services in the hospitality field (Kim et al , 2022). Mejia et al (2021) confirmed that IoT technologies such as wearables are significant in protecting hotel housekeepers' safety and health amid and post-COVID-19.…”
Section: Review Findingsmentioning
confidence: 83%
“…Thus, training programs are essential (Akyazi et al , 2020). According to Mejia et al (2021), to avoid COVID-19 and protect hotel housekeepers' safety and health, it is recommended for hotels to adopt and use a wearable technology solution which is an important part of IoT. In addition, robots are important amid and post-COVID-19 in hospitality to perform routine tasks, avoid virus transmission (Çakar and Aykol, 2021) and reduce employee–clients contact (McCartney and McCartney, 2020).…”
Section: Practical Implications and Recommendationsmentioning
confidence: 99%
“…Smart hospitality can help alleviate these challenges by eliminating repetitive and monotonous tasks; enhancing the work environment; reducing stress; and creating more interesting, fulfilling roles for employees (Ivanov et al , 2020; Liu and Hung, 2020). Smart technologies can also facilitate employee–customer interactions and elevate service effectiveness (Marinova et al , 2017) as well as help housekeeping staff to carry out tasks more safely (Mejia et al , 2021).…”
Section: Smart Hospitality Stakeholders: Reengineering Value Chains A...mentioning
confidence: 99%